2020
DOI: 10.21608/eajbsa.2020.110603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Seasons on the Royal Jelly Production Under Nasr City Conditions – Cairo - Egypt

Abstract: The study was executed at apiary of Plant protection Dept. Fac. of Agric. Al-Azhar Univ., Cairo, Egypt, during two successive years 2019 and 2020 to determine the effectiveness of different seasons on the acceptance rates of the larvae and royal jelly production. In the first year, the highest acceptance means for Italian hybrid 72.1 and 65.43% for Carniolan hybrid were recorded at midspring on the other hand, the lowest acceptance percentages means were 50.86 and 55.8 % recorded at early summer for Carniolan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The RJBs could produce ≥10 kg RJ/year/ colony, confirming the feasibility of selection for this trait [ 29 , 46 ]. The results were consistent with Hussain [ 45 ] who recorded that percentage of queen cell acceptance rate, RJ production per colony and cell cup was higher in Italian bee colonies than Carniolan bee colonies. In contrast, Şahinler and Kaftanoğlu [ 25 ] revealed that the average percentage of acceptance rate and production of RJ was higher in Carniolan followed by Mugla and Caucasian bees.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The RJBs could produce ≥10 kg RJ/year/ colony, confirming the feasibility of selection for this trait [ 29 , 46 ]. The results were consistent with Hussain [ 45 ] who recorded that percentage of queen cell acceptance rate, RJ production per colony and cell cup was higher in Italian bee colonies than Carniolan bee colonies. In contrast, Şahinler and Kaftanoğlu [ 25 ] revealed that the average percentage of acceptance rate and production of RJ was higher in Carniolan followed by Mugla and Caucasian bees.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study indicated that RJ production was significantly higher in summer seasons than winter seasons in both bee races. Hussain [ 45 ] revealed similar results that queen cell acceptance rate and RJ yield were higher in Italian bee hybrid than Carniolan bee hybrid during summer and winter seasons.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…RJ production higher in RJBs suggested that honey bees’ lines effect on larval acceptance and RJ productions [ 19 , 31 ]. Our results are in line with previous research, recorded that larval acceptance rate and per cell cup were 72.1% and 236.31 mg/cell cup for Italian bees and 65.43% and 187.24 mg/ cell cup in Carniolan bees [ 53 ]. Further, another study reported the mean larval acceptance rate and RJ yield was more in Carniolan than other races [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Njeru et al (2017) was reported that the larvae age at 12, 24, and 36 hours was higher of acceptance rate compared to 6 and 48 hours for Apis mellifera scutellata queen. The acceptance rate of larvae was affected by the raw material to make queen cells, food, and seasons (Khan et al 2021) and by honeybee species (Hussain et al 2020). The heavier emergence weight of 1 day old was supported by the higher acceptance rate in 1 day old than in 2 and 3 days old (Figure 3).…”
Section: Discussionmentioning
confidence: 95%